Biodiesel production potential of oleaginous Rhodococcus opacus grown on biomass gasification wastewater. (May 2017) - Goswami, Lalit; Tejas Namboodiri, M.M.; Vinoth Kumar, R.; Pakshirajan, Kannan; Pugazhenthi, G.
Abstract: This study examined the valorization of biomass gasification wastewater (BGWW) for lipids accumulation by Rhodococcus opacus and potential biodiesel application. Using synthetic mineral media based BGWW, the bacterium accumulated a maximum 65.8% (w/w) of lipids. 10% (v/v) inoculum size showed a more positive effect than 5% (v/v) inoculum size on both the chemical oxygen demand (COD) removal and lipid accumulation by R. opacus . Using the raw wastewater (untreated), the bacterium accumulated 54.3% (w/w) lipid with a wastewater COD removal efficiency of 64%. However, these values were further enhanced to 62.8% (w/w) and 74%, respectively, following supplementation of the wastewater with mineral salt media in the ratio 4:1. 1 H and 13 C nuclear magnetic resonance (NMR) spectroscopy analyses of the accumulated lipids revealed the presence of more saturated fatty acids than unsaturated fatty acids. Thermogravimetric analysis (TGA) of the accumulated lipids showed four thermal decomposition regions each with a good stability. Transesterification of the bacterial lipids to biodiesel and its properties revealed a very good potential of the strain for the production of biodiesel from PAH containing wastewater. Graphical abstract: Highlights: Biomass gasification wastewater is a cheap substrate for oleaginous R. opacus . Very high wastewater COD removal and lipid accumulation were achieved. Lipid characterization revealed more than 80% of saturated fatty acids content and good oxidation stability. Estimated properties of the biodiesel were within the biodiesel standards.